The Ergonomic Knowledge and Practice of Dental Students in a Tertiary Institution in South Africa - U. K. Moosa; A. Bhayat (International Journal of Dentistry)
Proper ergonomic practices are crucial practices to be considered when working on dental patients, and are often neglected during the dental students’ training. We aimed to assess the dental students’ knowledge of ergonomics as well the prevalence of their musculoskeletal pain. Methods. A cross sectional analytical study was conducted at a dental school in South Africa. The sample included all senior dental, and dental hygiene students registered in the 2021 academic year. A modified questionnaire using an online platform assessed the student’s level of practical and theoretical knowledge of ergonomics; their personal assessment of their competency in implementing ergonomics; and their prevalence of musculoskeletal pain. The knowledge scores were calculated to determine the overall scores. Data was analysed using the Statistical Package for the Social Sciences (SPSS). Ethical clearance was obtained from the Faculty Ethical Committee and all information was anonymous. Results. The response rate was 52% (n = 106), the mean knowledge score was 68%, and 53% reported to be able to successfully implement their ergonomic knowledge practically. The prevalence of musculoskeletal pain increased from 32% prior to entering dental school to 78% during dental school. Pain was most commonly reported to be on the back (77%), neck (51%), and shoulders (51%). Conclusion. The majority of students had an average level of knowledge regarding ergonomic principles, however, the practical application was poor. Many students reported to have suffered from back pain which seemed to have started since treating patients. The supervisors should educate and assist students to practice healthy ergonomic postures during clinical and pre-clinical sessions.